Congenital and Placenta Malaria and Newborn Birth Weight in Asymptomatic HIV Positive Pregnant Women at Term - Kuku-Kuye, Taiwo O.; Orekoya, Oluwaseun O.; Fabamwo, Adetokunbo O.; Akinola, Oluwarotimi I.; Olumodeji, Ayokunle M. (International Journal of Innovative Research in Medical Science, 2022)
Background: Human Immuno-deficiency Virus (HIV) and Malaria infection independently are major contributors to adverse perinatal outcomes in sub-Saharan Africa. A co-infection of both in pregnancy has been associated with more deleterious birth weight- related neonatal outcomes. We assessed for congenital malaria and evaluated the birth weights of babies born to HIV positive mothers with and without evidence of placenta malaria at term delivery. Methods: This was a comparative cross-sectional study in which 90 low-risk, HIV positive pregnant women on highly active retroviral therapy (HAART), asymptomatic for malaria, with uncomplicated delivery, at the Lagos State University Teaching Hospital, were consecutively recruited to have their maternal venous, placenta and newborn blood samples assessed following delivery for malaria. A placenta biopsy was also done to assess for features of placenta malaria. Data obtained were expressed in frequencies and percentages and variables were tested as appropriate using an independent t-test, chi-square and spearman’s correlation. The level of significance was set at p<0.05. Findings: The prevalence of placenta malaria and congenital malaria in the study was 11.1% and 0.0% respectively. Only 3.3% of the asymptomatic HIV positive, pregnant women at delivery had positive malaria tests of their venous blood samples. The mean neonatal packed cell volume at birth for women with and without placenta malaria was 43.6% and 44.9% respectively (p=0.044). The mean birth weight of the babies born to HIV positive women with and without placenta malaria was 2.7±0.2kg and 3.0±0.4kg respectively (p=0.008). The correlation between birth weight and CD4 count was positive but insignificant (r=0.069, p=0.515). Conclusion: Although, irrespective of placenta malaria status, congenital malaria is a rarity in babies of HIV positive pregnant women, the birth weight and packed cell volume of babies born to HIV positive women is significantly lower in this group of women with features of placenta malaria than in women without placenta malaria.